Factors Associated with Mothers’ Perceived Quality of Life among Young Children with Pneumonia in Dhaka, Bangladesh - Biswas, Happy Bandana; Chaimongkol, Nujjaree; Pongjaturawit, Yunee (International Journal of Human and Health Sciences (IJHHS), 2019)
Objective: This study aimed to examine factors associated with quality of life among young children with pneumonia. A simple random sampling was used to recruit a sample of 100 mothers of young Bangladeshi children with pneumonia admitted in pediatric wards at the Dhaka Medical College Hospital, Dhaka, Bangladesh from January to March 2014. Materials and Methods: Research instruments included a demographic questionnaire, the perceived severity of illness’ scale, the Parenting Stress Index and the quality of life scale for Pneumonia Module. Their reliability were .79, .91 and .77, respectively. Data were analyzed by using descriptive statistics, Pearson correlation, independent t-test and one-way ANOVA. Results: Results revealed that mean total score of quality of life of the children with pneumonia was 50.05 (S.D. = 11.11), and at a moderate level. There was a significant relationship between maternal stress and quality of life of pneumonia children (r = -.48, p < .01). However, there was no relationship between perceived severity of illness and quality of life. No significant difference of quality of life of pneumonia children was also found between levels of maternal education and yes/no co-morbidity. Conclusion: These findings indicate that maternal stress is a significant factor. Pediatric nurses and related health care providers should plan and intervene to lessen stress of the mothers, and that would result in increasing quality of life of young children with pneumonia. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 196-200